X‐ray and synchrotron diffraction studies of 2‐(pyridin‐2‐yl)‐1, 10‐phenanthroline in the role of ligand for two copper polymorphs or hydrogen bonded with 2, 2, 6, 6‐tetramethyl‐4‐oxopiperidinium hexafluorophosphate. (17th April 2013) - Krause, Jeanette A.; Zhao, Daoli; Chatterjee, Sayandev; Yeung, Bonnie M.; Connick, William B.; Collins, Sibrina N.
Abstract : Different extended packing motifs of dichlorido[2‐(pyridin‐2‐yl)‐1, 10‐phenanthroline]copper(II), [CuCl2 (C17 H11 N3 )], are obtained, depending on the crystallization conditions. A triclinic form, (I), is obtained from dimethylformamide–diethyl ether or methanol, whereas crystallization from dimethylformamide–water yields a monoclinic form, (II). In each case, the Cu II centre is in a five‐coordinate distorted square‐pyramidal geometry. The extended packing for both forms can be described as a highly offset π‐stacking arrangement, with interlayer distances of 3.674 (3) and 3.679 (3) Å for forms (I) and (II), respectively. The reaction of diprotonated Pt(tmpip2 NCN)Cl [tmpip2 NCN = 2, 6‐bis(2, 2, 6, 6‐tetramethylpiperidylmethyl)benzyl] with AgPF6 under acidic conditions, followed by the addition of 2‐(pyridin‐2‐yl)‐1, 10‐phenanthroline, results in a hydrogen‐bonded cocrystal, 2, 2, 6, 6‐tetramethyl‐4‐oxopiperidinium hexafluorophosphate–2‐(pyridin‐2‐yl)‐1, 10‐phenanthroline (1/1), C9 H18 NO + ·PF6 − ·C17 H11 N3, (III). The extended packing maximizes π–π interactions in a parallel face‐to‐face arrangement, with an interlayer stacking distance of 3.4960 (14) Å.